“PROPUESTA DE USO Y OCUPACIÓN DEL SUELO EN EL LÍMITE URBANO DEL CANTÓN CHUNCHI” - Landy Alvarez, Sandra Vanessa (2019)
The process of urban expansion is manifested in the informal and unplanned growth of the villages, which is why the intervention on the urban limit of the Chunchi canton is necessary, considering the socioeconomic, environmental and political development, in order to successfully interfere in each sector of the canton it is necessary to know it, know what its problems are, as well as the strengths it possesses. Through the diagnosis made in each of the elements that intervene in the urban area and the identification of the current state of the built environment, focused mainly on the use and occupation of urban land, a proposal of an urban limit is proposed, which contemplates areas in the process of expansion, also proposes the sectorization of the urban area, to subsequently set guidelines, based on the population projected to the year 2020 and the sizing of each planning sector; that rule the use and occupation of the soil of each proposed sector, seeking to preserve the current state and the homogeneity of the area. Achieving quantitative and qualitative data that control the urban expansion and that also coincide with existing buildings, this control is done in the following aspects: main and complementary uses, types of housing implementation, forms of occupation, minimum and maximum lots, in addition to the building height, finally obtaining an urban model with which an organized and regulated growth is achieved.